2023
DOI: 10.1021/acs.macromol.2c02243
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Productive Upcycling CO2 into Polycarbonate Polyols via Borinane-Based Bifunctional Organocatalysts

Abstract: We herein report the synthesis of commercially attractive low molar mass polycarbonate polyols obtained through the ring-opening copolymerization of CO 2 and epoxides, using a series of borinane-based bifunctional organocatalysts in the presence of chain transfer agents (CTAs). These catalysts enable CO 2 /epoxide copolymerizations with high linear vs cyclic selectivity and outstanding productivity for both poly(cyclohexane carbonate) polyols (18.2 kg/g catalyst) and poly(ether propylene carbonate) polyols (1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 55 publications
(69 reference statements)
0
15
0
Order By: Relevance
“…However, the catalytic efficiency was relatively low and the molecular weight of the reported copolymer needed further improvements. In contrast to binary organoborane based Lewis pair, we and others showed that one‐component organoborane based Lewis pair exhibited enhanced activity in the ROP 35,36,39–43 …”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, the catalytic efficiency was relatively low and the molecular weight of the reported copolymer needed further improvements. In contrast to binary organoborane based Lewis pair, we and others showed that one‐component organoborane based Lewis pair exhibited enhanced activity in the ROP 35,36,39–43 …”
Section: Introductionmentioning
confidence: 65%
“…In contrast to binary organoborane based Lewis pair, we and others showed that one-component organoborane based Lewis pair exhibited enhanced activity in the ROP. 35,36,[39][40][41][42][43] To diversify the reaction scope of ROAP and demonstrate the synergistic effects on enhancing the activity of one-component organoborane based Lewis pair, we herein attempted to apply PBB-Br for the copolymerization of PO and OPA to generate degradable PPO with acetal backbone.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the heterogeneous double metal cyanide catalyst has the potential in the preparation of colorless CO 2 ‐polyol, whereas the molecular weight is hard to below 1200 g mol −1 [13] . Very recently, Feng and Gnanou reported borinane‐based bifunctional organocatalysts ( p =200), achieving a low molecular weight of 1600 g mol −1 [14] . Collectively, it remains challenging to prepare colorless ULMW CO 2 ‐polyols (<1000 g mol −1 ), which is useful for the synthesis of rigid polyurethane foams (high crosslinking density).…”
Section: Introductionmentioning
confidence: 99%
“…[13] Very recently, Feng and Gnanou reported borinane-based bifunctional organocatalysts (p = 200), achieving a low molecular weight of 1600 g mol À 1 . [14] Collectively, it remains challenging to prepare colorless ULMW CO 2 -polyols (< 1000 g mol À 1 ), which is useful for the synthesis of rigid polyurethane foams (high crosslinking density).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many reviews have summarized the progress of research on aromatic polycarbonates synthesized from BPA and diphenyl carbonate and aliphatic polycarbonates synthesized from epoxide and CO 2 . [37][38][39][40][41][42][43][44][45] However, there are no reviews that provide a systematic summary of bio-based PCs to our knowledge. So in this review, we give a comprehensive introduction to two representative bio-based PCs, poly(isosorbide carbonate)s and poly(limonene carbonate)s. A brief introduction of the bioderived monomers is presented in the rst section.…”
Section: Introductionmentioning
confidence: 99%